The Dynamics of Well Being on the Young Women who Smoke as a Coping Stress - RUDI PURWANA (Jurnal Kesehatan LLDikti Wilayah 1 (JUKES), 2022)
Smoking is a lifestyle phenomenon for most people today and even more so for teenagers. Where adolescence is a period of transition, adolescents become unstable and easily influenced. Therefore, in this uncertain condition, adolescents are easy to experience problems and behave negatively because their emotions have not been fully formed, one of which is smoking. Based on data from Riskesdas 2013, the average female smokers were 2.7% and 2.1%, respectively. This study aims to determine and explain the frequency of adolescent well-being, coping with stress in adolescents, dynamics of well-being (welfare) in adolescent girls who smoke as coping with stress. The research design used qualitative, using questionnaires, interviews (in-depth interviews) and observation. The results showed that the frequency of well being low was 1 person (25%) and well being was high as much as 3 people (75%). The occurrence of stress is motivated by economic factors, sadness, divorce, bad habits, pressure from family. So that young women feel depressed and choose smoking coping or strategies with emotional-focus coping; escampe (avoiding). The strategy is cognitive with logical analysis, positive reappraisal, acceptance-resignation, alternative rewords, emotional discharge. It is recommended for adolescents who smoke to be used as input or education materials in information sources regarding the dynamics of well being and stress management.